2021
DOI: 10.14258/jcprm.2021027440
|View full text |Cite
|
Sign up to set email alerts
|

Features of Microelements and Low-Molecular Weigh Antioxidants Accumulation in Plants Ofthe Genus Rosa L.

Abstract: Wild roses are an important group of plants used as row material for pharmaceutical, cosmetic and food industries. The aim of this study was to determine the microelements (Mn, Fe, Zn, Cu, Cr, Ni, Pb, Co, Cd) content and distribution in the aboveground and underground parts of the Rosa acicularis, R. davurica, R. rugosa, growing in Baikal region. It was found that R. rugosa plants are characterized by a higher Cu content and a low level of Mn; the hips of these plants also accumulate Fe, Zn, and Co. In the sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…It was found that R. rugosa (growing in Baikal region) plants are characterized by a higher Cu content and a low level of Mn; the hips of these plants also accumulate Fe, Zn, and Co in the sepals, leaves, stems and roots. It has been shown that rose hips, as well as the leaves and stems of Rosa rugosa, can serve as a potential source of Mn, Cr, and Co for the human body [85]…”
Section: Resultsmentioning
confidence: 99%
“…It was found that R. rugosa (growing in Baikal region) plants are characterized by a higher Cu content and a low level of Mn; the hips of these plants also accumulate Fe, Zn, and Co in the sepals, leaves, stems and roots. It has been shown that rose hips, as well as the leaves and stems of Rosa rugosa, can serve as a potential source of Mn, Cr, and Co for the human body [85]…”
Section: Resultsmentioning
confidence: 99%
“…Typically, compounds such as citric acid and sodium borohydride, which can be toxic, are employed in the reduction process. However, recent studies have explored alternative methods, utilizing extracts from natural sources such as honey, polysaccharides, microorganisms, and plants like Rosa rugosa, Terminalia catappa, and Zingiber officinale for gold nanoparticle synthesis [5][6][7][8]. Interestingly, the concentration of the reducing agents in these methods has been shown to influence the size and shape of the resulting nanoparticles.…”
Section: Introductionmentioning
confidence: 99%